"Official View" on Glucocorticoids in Rheumatoid Arthritis: A Systematic Review of International Guidelines and Consensus Statements. Issue 8 (10th July 2017) - Palmowski, Yannick; Buttgereit, Thomas; Dejaco, Christian; Bijlsma, Johannes W.; Matteson, Eric L.; Voshaar, Marieke; Boers, Maarten; Buttgereit, Frank
Abstract : Objective: To describe the perception of the current role of systemic glucocorticoids in the management of rheumatoid arthritis (RA) by examining their importance and the current level of evidence in recent guidelines, and to identify open questions to be addressed in future guidelines and research projects. Methods: We conducted a systematic literature review using the databases Ovid Embase, PubMed Medline, and Cochrane Library for guidelines on the pharmacologic treatment of RA. Retrieved articles were evaluated regarding their quality using the Appraisal of Guidelines for Research and Evaluation II tool and scrutinized for all relevant information concerning the use of glucocorticoids. Results: All guidelines agree that glucocorticoids, especially if given at low doses and for a short duration, are an appropriate option in the treatment of RA. However, many recommendations remain vague, as reliable and detailed evidence is scarce. Important aspects of glucocorticoid therapy are partially or completely neglected, and the existing nomenclature is not used uniformly. Quality evaluation revealed flaws in many articles, concerning not only glucocorticoid‐specific recommendations but also guideline quality in general. Conclusion: Current recommendations for use of glucocorticoids in the management of RA are suboptimal. More rigorous evaluation of doses, timing, and duration of their use is needed. Existing nomenclature on glucocorticoid therapy should be used uniformly.